Optimasi Proses Multi-Pass Equal Channel Angular Pressing dengan Simulasi Komputer - Choiron, Moch. Agus; Anam, Khairul; Prasetyo, Totok Tri (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2014)
UFG (Ultra-fine grained) material is a material with a grain size between 10 nm to 1000 nm were developed to improve the quality of the material microstructure byreducing the grain size. Equal Channel Angular Pressing (ECAP) is a method to produce the UFG material by utilizing the shear stress on the material. Shear stress distribution in the material as it passes through the channel intersection is important to investigate so that it can be known the die design that can produce a uniform shear stress distribution in the material. In this study, computer simulation of multi-pass ECAP is carried out as the initial prediction for reducing the trial- error ECAP process. Multi-pass ECAP process is modeled with software based on Finite Element Method (FEM). Optimization is done with L9 Taguchi which parameters arenumber of pass, angle of intersection, outer fillet, and friction coefficient. By measuring the distribution of shear stress and plastic strain on the model will be generated optimization of multi-pass ECAP process.In the present study, the optimum setting for equal channel angular pressing prosses are pass of 6,intersection angle of 90 , outer fillet radii of 2 mm and coefficient friction of 0,1.Keywords: ECAP, multi-pass, Taguchi method, shear stress, plasticstrain.